KREATIF, INDAH DAN BERPELUANG BISNIS LEWAT KOKEDAMA - Hommy Dorthy Ellyany Sinaga; Jeperson Hutahaean; Yessica Siagian (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The community service activity is targeted to an organization of Rajagukguk family member in Kisaran, Asahan. It is aimed to provide the kokedama skill training to make decorative plants in which this skill will be able to give knowledge and skill to decorate the house yard or area more beautiful. The community service activity is held for two days, 24th-25th April 2020 through online learning media as in COVID pandemic condition, the government has declared to do stay at home and social distancing. Then the method used is to make a video of how to make kokedama and then share the video to the community of Rajagukguk family member. All the members responded positively to this training activities provided.